Assessment of PrBaCo2O5+d + Sm 0.2Ce0.8O1.9 composites prepared by physical mixing as electrodes of solid oxide fuel cells - Chen, D.; Ran, R.; Shao, Zongping (Elsevier SA, 2010)
The performance of PrBaCo2O5+d + Sm 0.2Ce0.8O1.9 (PrBC + SDC) composites as electrodes of intermediate-temperature solid oxide fuel cells is investigated. The effects of SDC content on the performance and properties of the electrodes, including thermal expansion, DC conductivity, oxygen desorption, area specific resistance (ASR) and cathodic overpotential are evaluated. The thermal expansion coefficient and electrical conductivity of the electrode decreases with an increase in SDC content. However, the electrical conductivity of a composite electrode containing 50 wt% SDC reaches 150 S cm-1 at 600 °C. Among the various electrodes under investigation, an electrode containing 30 wt% SDC exhibits superior electrochemical performance. A peak power density of approximately 1150 and 573 mW cm-2 is reached at 650 and 550 °C, respectively, for an anode-supported thin-film SDC electrolyte cell with the optimal composite electrode. The improved performance of a composite electrode containing 70 wt% PrBC and 30 wt% SDC is attributed to a reduction in the diffusion path of oxygen-ions within the electrode, which is a result of a three-dimensional oxygen-ion diffusion path in SDC and a one-dimensional diffusion path in PrBC. © 2010 Elsevier B.V.